2015
DOI: 10.1302/0301-620x.97b1.34525
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of stress fracture following peri-acetabular osteotomy

Abstract: Stress fractures occurring in the pubis and ischium after peri-acetabular osteotomy (PAO) are not well recognised, with a reported incidence of 2% to 3%. The purpose of this study was to analyse the incidence of stress fracture after Bernese PAO under the care of two high-volume surgeons. The study included 359 patients (48 men, 311 women) operated on at a mean age of 31.1 years (15 to 56), with a mean follow-up of 26 months (6 to 64). Complete follow-up radiographs were available for 348 patients, 64 of whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 17 publications
2
26
0
1
Order By: Relevance
“…There were no patients who had further surgery for impingement nor any stress fractures at the osteotomy sites [13]. We would hence advise to err on the side of caution regarding the amount of correction achieved.…”
Section: Discussionmentioning
confidence: 99%
“…There were no patients who had further surgery for impingement nor any stress fractures at the osteotomy sites [13]. We would hence advise to err on the side of caution regarding the amount of correction achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Another important issue has been explored by Malviya et al, 35 who analysed the incidence of stress fracture after PAO under the care of two high-volume surgeons (359 patients included, mean age 31.1 years (15 to 56), with a mean follow-up of 26 months). Eighteen percent of the patients developed a stress fracture of the inferior pubic ramus, which was noted radiologically at a mean of 9.1 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 25 - 33 The learning curve related to the occurrence of complications affects the outcome in some studies. 8 , 29 , 34 Stress fracture of the ischium has recently been reported to occur in 18% 35 and obesity has recently been shown to increase the risk of a serious complication by 11 times. 36 …”
Section: Developmental Dysplasia Of the Hip: Periacetabular Osteotomymentioning
confidence: 99%
“…54,55 The risk of major arterial injury is low with MSP and MIS approaches as compared with ilioinguinal approach which has been reported to have a higher incidence of femoral artery thrombosis. 11,27 Malviya et al 56 analysed the incidence of stress fracture after PAO in 359 patients. They found that 18.4% developed a stress fracture of the inferior pubic ramus, which was noted at a mean of 9.1 weeks after surgery.…”
Section: Not Reportedmentioning
confidence: 99%